Does [18F]FDG and [18F]AV1451 PET predict neurodegeneration?. (1st February 2022) - Nowell, Joseph; Young, Megan; Raza, Sanara; Livingston, Nicholas R; Crook, Harry; Edison, Paul
Abstract: Background: [18F]FDG PET is a well‐established and valuable biomarker in the assessment of neurodegenerative disorders, with high diagnostic utility, wide accessibility, and relatively low costs. Recent advances in PET imaging technology now allow for the in vivo exploration of tau deposition. However, it is still being debated which of [18F]FDG PET or [18F]AV1451 PET better predicts neurodegeneration. This study aimed to evaluate [18F]FDG PET and [18F]AV1451 PET imaging in predicting grey matter atrophy in patients with cognitive impairment. Method: 190 patients with mild cognitive impairment or Alzheimer's disease (Mean age = 74.3 years, SD = 8.04) were evaluated from the Alzheimer's Disease Neuroimaging Initiative (adni.loni.usc.edu). All participants completed a T1‐weighted MPRAGE MRI, [18F]AV1451 and [18F]FDG PET scans. Standard uptake ratio values were calculated in SPM12 to identify the glucose metabolic rate and tau deposition within the medial temporal lobe. Whole brain grey matter volumes were obtained from processed data from ADNI. Pearson's correlation coefficients were calculated to assess the relationship between imaging modalities. Result: There was a significant negative association between [18F]AV1451 uptake in the medial temporal lobe and whole brain grey matter volume (r = ‐0.288, p = 0.001). A stronger positive relationship was identified between medial temporal lobe [18F]FDG uptake and whole brain grey matter volume (r = 0.444, p < 0.001). Conclusion: This study demonstrated that regional FDG and tau tracer uptake in patients with cognitive impairment both display a significant relationship with total grey matter volume. Whilst both tracers show utility in predicting a patient's level of neurodegeneration, glucose metabolism as indicated by [18F]FDG PET appears to have a closer relationship to grey matter atrophy than PET markers of tau deposition.